The Relationship between Public Debt, Government Efficiency, and Corruption Control on Fiscal Sustainability in Indonesia - Haryono Haryono (West Science Journal Economic and Entrepreneurship, 2025)
This study explores the relationship between public debt, government efficiency, and corruption control in the context of fiscal sustainability in Indonesia. Using a normative qualitative research approach, the study analyzes legal frameworks, government policies, and institutional reports to assess how these three factors interact and affect fiscal health. The findings indicate that while Indonesia’s public debt remains within manageable limits, challenges in government efficiency and corruption control undermine the optimal use of public resources and exacerbate fiscal deficits. The analysis highlights that inefficient government operations, combined with corruption, contribute to the misallocation of debt-financed resources, thereby hindering fiscal sustainability. The study concludes that improving debt management, enhancing government efficiency, and strengthening anti-corruption measures are essential for ensuring long-term fiscal stability in Indonesia.